Comparative Clinical Evaluation of Vyoshadi Guggulu and Triphala Churna on Medo Roga w.s.r. to Dyslipidemia (International Journal of Ayurveda and Pharma Research, 2025)
Medo Roga (dyslipidemia), a disorder of lipid metabolism, is a significant global health concern. This study aimed to compare the efficacy of Vyoshadi Guggulu and Triphala Churna in managing Medo Roga. A randomized open-label clinical trial was conducted with 60 patients over 42 days. Lipid profile, fasting blood sugar, serum creatinine, blood urea, SGOT, and SGPT were assessed. Subjective symptoms such as Kshudra Vyavaya (difficulty in sexual activities), Daurbalya (fatigue), Sweda Abadha (excessive sweating), Durgandha (bad body odor), Athi Kshuth (excessive hunger), and Pipasa Athiyoga (excessive thirst) were evaluated before and after treatment. In the Vyoshadi Guggulu group (Group A), serum total cholesterol decreased from 248.9467±4.325mg/dl before treatment to 212.8933± 4.070mg/dl after treatment (p=0.000). In the Triphala Churna group (Group B), the levels were 250.8667±3.954 mg/dl before treatment and 227.5333±3.049mg/dl after treatment (p=0.000). Subjective parameters showed statistically significant reductions in both groups. Vyoshadi Guggulu was superior in reducing lipid levels and subjective symptoms, whereas Triphala Churna showed greater efficacy in enhancing renal function. It can be concluded that both Vyoshadi Guggulu and Triphala Churna are effective in the management of Medo Roga.